2002
DOI: 10.1152/jn.00350.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Developmental Changes of Na+Currents of Petrosal Neurons With Projections to the Carotid Body

Abstract: Carotid body chemoreceptors transduce a decrease in arterial oxygen tension into an increase in spiking activity on the sinus nerve, and this response increases with postnatal age over the first week or two of life. Previous work from our laboratory has suggested a major role of axonal Na+ channels in the initiation of afferent spiking activity. Using RT–PCR of the petrosal ganglia we identified Na+ channel TTX-S isoforms Nav1.1, Nav1.6, and Nav1.7 and the TTX-resistant (TTX-R) isoforms Nav1.8 and Nav1.9 at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 48 publications
3
31
0
Order By: Relevance
“…Donnelly and his colleagues explored the properties of voltage-sensitive Na + -currents in rat PG neurons which were back-labeled with a fluorescent dye applied to the carotid body (Cummins et al 2002). These authors reported that in ~80% of chemoafferent neurons >95% of the Na + -current was TTX-sensitive.…”
Section: Inflammation and Primary Sensory Neuron Excitabilitymentioning
confidence: 99%
“…Donnelly and his colleagues explored the properties of voltage-sensitive Na + -currents in rat PG neurons which were back-labeled with a fluorescent dye applied to the carotid body (Cummins et al 2002). These authors reported that in ~80% of chemoafferent neurons >95% of the Na + -current was TTX-sensitive.…”
Section: Inflammation and Primary Sensory Neuron Excitabilitymentioning
confidence: 99%
“…It is therefore possible that the TRPV1 channel may play a role in the acid-sensitive responses of the soft palate taste buds (Leffler et al 2006;Liu et al 2004). In support of this possibility, TRPV1-immunoreactive fibers have been described in soft palate taste buds (Kido et al 2003), and application of capsaicin to the palate evokes a burning sensation and reflex secretion of saliva (Dunér-Engström et al 1986). …”
Section: Discussionmentioning
confidence: 95%
“…Na ϩ currents in GG neurons. Although Na ϩ channels have been thoroughly characterized in dorsal root (Cummins et al 1999;Roy and Narahashi 1992;Rush et al 1998) and trigeminal sensory ganglia (Kim and Chung 1999;Liu et al 2001), both of which innervate a variety of sensory receptors including nociceptors, the current study is the first study of voltagegated Na ϩ channel in the GG. Two distinctly different TTXsensitive Na ϩ currents differentiated by the amplitudes of TTX-S and TTX-R components were expressed in CT, GSP, and PA neurons.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to better resolve the basis for these differences, patch clamp recordings were undertaken on neurons dissociated from petrosal ganglia, which had been pre-labeled from the carotid body (Cummins et al, 2002). Measurements of Na + currents in these neurons showed a uniform population with half-activation potential of −23mV and half inactivation potential of −70mV.…”
Section: Sodium Channels In Synaptic Transmissionmentioning
confidence: 99%